Paidéia e retórica no diálogo Fedro de Platão - Oliveira, Lucas Mafaldo (2010)
This study presents a study on Plato's Phaedrus , with the purpose of discussing the possibility of interpreting this dialogue as a discussion on the greek notion of paideia.. We believe to find evidence to support this claim both in the cultural background of the dialogue and in its text. As background evidence, we point to the fact that Rhetoric had become the major disciplined studied in Athens in Plato's time, largely because democratic instituitions favored its practice. As text evidence, we point out that the story of the Phaedrus can be read as the story of how Socrates leads Phaedrus's soul toward philosophy. Therefore, we believe that Plato's main goal with this dialogue is to discuss Rhetoric and present the philosophical perspective on the possibility of an art of speechmaking. In order to achieve this, Plato presents an analyses of current Rhetoric, explains his conception of dialectic, and debate the relation between extemporaneous and written speech. We believe that all those elements serve the larger purpose of providing the background to discuss the cultural education of the Athenians